2014
DOI: 10.1155/2014/808759
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Assessment of the Indian Children with Congenital Sensorineural Hearing Loss

Abstract: Introduction. Congenital sensorineural hearing loss is one of the most common birth defects with incidence of approximately 1 : 1000 live births. Imaging of cases of congenital sensorineural hearing loss is frequently performed in an attempt to determine the underlying pathology. There is a paucity of literature from India and for this reason we decided to conduct this study in Indian context to evaluate the various cochleovestibular bony and nerve anomalies by HRCT scan of temporal bone and MRI with 3D scan o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…Similar result was observed in Chaturvedi et al, where, 16.7% patients showed various types of congenital inner ear malformations. 8 In our study, cochlea/ cochlea-vestibular deficiency, endolymphatic duct dilatation, and vestibule/SCC anomaly were found in 12.5, 10.5, and 5.8%, respectively, as compared with 25, 12, and 7% reported by Lin et al 9 Our finding is also comparable with Agarwal et al 10 Surgical difficulty was negatively associated with higher size of EAC, distance between tympanic segment of facial canal to EAC, and BTA (p < 0.05), which indicated that patients with narrow size of the above parameters increase the difficulty of the surgery while no association was observed with age and sex (p > 0.05). Similarly, poor mastoid pneumatization, abnormal middle ear cavity, and abnormal vestibule/vestibular aqueduct were more commonly associated with surgical difficulty (p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Similar result was observed in Chaturvedi et al, where, 16.7% patients showed various types of congenital inner ear malformations. 8 In our study, cochlea/ cochlea-vestibular deficiency, endolymphatic duct dilatation, and vestibule/SCC anomaly were found in 12.5, 10.5, and 5.8%, respectively, as compared with 25, 12, and 7% reported by Lin et al 9 Our finding is also comparable with Agarwal et al 10 Surgical difficulty was negatively associated with higher size of EAC, distance between tympanic segment of facial canal to EAC, and BTA (p < 0.05), which indicated that patients with narrow size of the above parameters increase the difficulty of the surgery while no association was observed with age and sex (p > 0.05). Similarly, poor mastoid pneumatization, abnormal middle ear cavity, and abnormal vestibule/vestibular aqueduct were more commonly associated with surgical difficulty (p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, Agarwal SK et al reported a frequency of 13.93%, indicating that probably population in this subcontinent was less prone to develop IEM’s. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 While in an Indian study by Agarwal SK et al the prevalence of cochlear anomaly was 73%, 87.1% had vestibular malformations, 56.4% had vestibular aqueduct malformation, 30.7% were with IAC anomaly and 29.4% had 8 th CN anomalies. 17 In an imaging study by El Sheikh E et al cochlear hypoplasia the commonest (4.5%), followed by common cavity (3%), IP-1 (3%), IP-2 (16.7%), IP-3 (7.6%), posterior rotated cochlea (6.1%), dilated vestibule (3%), isolated SCC hypoplasia (3.03%), SCC hypoplasia with common cavity (3.03%), dysplastic SCC (6.8%), dilated IAC (4.5%), hypo-plastic IAC (18.2%), VCN hypoplasia (18.2%), isolated EVA (36.4%). 18 Also in a study by Dhanasingh A, found normal anatomy in four, enlarged vestibular aqueduct in 3, cochlear aplasia in 2, IP-I in 8, IP-II in 3, IP-III in four, CH in 17, common cavity (CC) in 5.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent imaging techniques have revealed inner ear malformations in a relevant percentage of patients affected by SHL. The data, reported in the scientific literature, mainly concern the paediatric population with a reported prevalence of inner ear malformations in children with profound SHL between 14-30% 15 . However, minor malformations or malformations limited to the membranous labyrinth, not detectable with common diagnostic tools, may be responsible for some cases of SHL of unknown origin.…”
Section: Discussionmentioning
confidence: 99%